(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
This study adopted autoethnography as a research methodology to relive and reflect on my experiences as a White Afrikaner girl in a history class during the apartheid era in South Africa. This paper focuses on how the grand narratives of Afrikaner Nationalist ideologies and Whiteness in South Africa influenced girlhood or girl-becoming within the History classroom during apartheid in the late 1980s. This paper purposefully interrogates how ideologies of white supremacy, such as ordentlikheid (ethnicised respectability), found their way into the micro-context of a primary school history classroom through small acts of oppression. Epistemologically, I underpin this this paper by an interpretative paradigm to justify the meaning-making of personal experiences, which form the core of this paper. Methodologically, the study adopted a qualitative approach, and the research design comprised of an autoethnography. Data consisted of a personal narrative developed from a reflective piece of personal free writing into a crafted story by relying on memory work and checked by verisimilitude to remember specific details. I was the sole participant in that I generated the data through my narrative. An analysis of the findings showed ‘place’ as predominant convergence of identity marker, namely the place of ‘outsider-girlhood’ within the socio-educational context and intersectionality as Nationalist influence on white girlhood. I conclude the paper with my final reflections as a form of meaning-making.